Case Report: Kejadian Luar Biasa Keracunan - Anita Nugrahaeni; Dewi Rachmawati (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background of study: There has been an increase in cases of suspected food poisoning in Lamuk Village, Kaliwiro District, Wonosobo Regency, Central Java Province. This case report will describe the events and factors that caused of food poisoning outbreak. The epidemiological investigation was carried out by the Health Office Team by investigating all participant who consuming food at Kartini’s Day Methods: They were grouped into cases and controls, in cohorts followed by the development of symptoms. The collected data was then analyzed using bivariate and multivariate statistics to determine the factors that cause poisoningResults: The results showed that residents who consumed fried chili sauce of chicken liver (p 0.001) had higher than a risk of poisoning 14.58 times. In addition, consuming “gudeg” (p = 0.021) increases the risk of poisoning 2.03 times.Conclusion: The most dominant factor was consumed fried chili sauce of chicken liver and was supported by laboratory results that showed the presence of Enterobacter aerogenes. The steps to overcome and prevent outbreaks have been done well.Keywords: Food poisoning; outbreak; epidemiological investigation